2021
DOI: 10.1128/msystems.00702-20
|View full text |Cite
|
Sign up to set email alerts
|

Sputum Proteome Signatures of Mechanically Ventilated Intensive Care Unit Patients Distinguish Samples with or without Anti-pneumococcal Activity

Abstract: Mechanically ventilated patients are at risk of contracting pneumonia. Therefore, these patients often receive prophylactic systemic antimicrobial therapy. Intriguingly however, a previous study showed that antimicrobial activity in bronchoalveolar aspirates (here referred to as “sputa”) from ventilated patients was only partially explained by antibiotic therapy. Here we report that sputa from these patients presented distinct proteome signatures depending on the presence or absence of antimicrobial activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The determination of Ply-specific antibody titers in IVIG and human plasma samples was performed via a Luminex-based serological assay described recently. 20 In brief, recombinant pneumolysin was immobilized on xMAP MagPlex beads (Luminex, United States), which were incubated with fourfold serially diluted IVIG (98% IgG; Privigen, CSL Behring, United States) or plasma samples (seven dilutions ranging from 1:50 to 1:204,800). Detection of primary antibody binding was enabled by incubation with an R-Phycoerythrin-labeled anti-human IgG (Jackson ImmunoResearch Europe Ltd, Ely, United Kingdom) followed by measurement in the FLEXMAP 3D (Luminex, United States).…”
Section: Methodsmentioning
confidence: 99%
“…The determination of Ply-specific antibody titers in IVIG and human plasma samples was performed via a Luminex-based serological assay described recently. 20 In brief, recombinant pneumolysin was immobilized on xMAP MagPlex beads (Luminex, United States), which were incubated with fourfold serially diluted IVIG (98% IgG; Privigen, CSL Behring, United States) or plasma samples (seven dilutions ranging from 1:50 to 1:204,800). Detection of primary antibody binding was enabled by incubation with an R-Phycoerythrin-labeled anti-human IgG (Jackson ImmunoResearch Europe Ltd, Ely, United Kingdom) followed by measurement in the FLEXMAP 3D (Luminex, United States).…”
Section: Methodsmentioning
confidence: 99%
“…A preliminary study found that the BAL fluid from 53% of patients under mechanical ventilation showed antimicrobial activity against three indicator bacteria ( Streptococcus pneumoniae, Staphylococcus aureus, and Streptococcus anginosus ) [24]. In a follow-up study, the authors performed a proteome analysis of the BAL and found that the antipneumococcal activity was associated with higher levels of proteins involved in innate immunity (complement and apolipoprotein-associated) [25 ▪▪ ]. Therefore, these different signatures of proteome and immunoproteome in BAL could explain at least partially differences in the risk of VAP development.…”
Section: Diagnosis Of Infectionmentioning
confidence: 99%